Trade Agreements as Endogenously Incomplete Contracts - Horn, Henrik; Maggi, Giovanni; Staiger, Robert W (American Economic Review, 2010)
We propose a model of trade agreements in which contracting is costly, and as a consequence the optimal agreement may be incomplete. In spite of its simplicity, the model yields rich predictions on the structure of the optimal trade agreement and how this depends on the fundamentals of the contracting environment. We argue that taking contracting costs explicitly into account can help explain a number of key features of real trade agreements. (JEL D86, F13)